Emergence of Contrast of Cognitive-Valuing Features of Mathematics Across Global Classrooms - Joshua Edson Gorme Ordiz (International Journal on Emerging Mathematics Education, 2020)
Processes and patterns in mathematics education are shaped into dynamic complex systems â€“ referred to as a new structure because of the close interplay and networks of different social atoms. The study attempts to understand the interactions at the macro level using exploratory data analysisÂ  of secondary data from an international assessment organization in order to discover and fathom the interrelationship of the characteristics namely achievement in mathematics and valuing attitude towards math. Findings showed that global classroom displayed a decline of performance as the valuing to the discipline intensifies. Further analysis found out that presently, the nature of valuing is extrinsic which focuses in the practical use of the subject. With this, behavior in learning mathematics is not positive when geared towards usefulness; but it will dramatically change the achievement when approach is modified to being a desirable disciple.